Pendampingan Implementasi Alat Peraga “PATUNG” Papan Hitung: Upaya Meningkatkan Hasil Belajar Siswa - Syarifah Fauziyah; Putri Yulia; Vini Avrilia Nasution; Silvia Efendi (SIGMA : Jurnal Sinergi Mengabdi, 2026)
This community service aims to implement the use of the Counting Board (PATUNG) teaching aid in improving the mathematics learning outcomes of Grade VII students, especially on materials related to integer and fraction arithmetic operations. The method used is the Implementation and Evaluation Method, which combines the implementation of the use of teaching aids, direct student practice, and evaluation of learning products. The subjects of this community service were 17 grade VII students of Miftahul Iqrar Islamic Boarding School. The research instrument was a student learning outcome test. The results of the community service showed that after the implementation of the PATUNG media, students' learning outcomes increased from an average pretest of 80.13 to an average posttest of 93.33. In addition, students played an active role in the learning process by directly trying out the PATUNG teaching aid to solve the problems given, thus fostering self-confidence in working on integer material. Therefore, it can be concluded that the use of the "Patung" teaching aid Counting Board can improve student learning outcomes. The implications of this study confirm that the application of concrete teaching aids such as STATUES can effectively overcome the abstract nature of mathematics and significantly improve students' understanding and learning outcomes.